Design of hydrodynamic cavitation assisted intensified tertiary treatment unit for effective degradation of organic micropollutants in pharmaceutical industrial effluent: a case study with triclosan - Mishra, Birupakshya; Mukherjee, Anupam; Mullick, Aditi; Bhandari, Vinay M.; Moulik, Siddhartha (Journal of Water Process Engineering, 2022)
Increasing occurrence of micropollutants and trace amount of persistent organic contaminants (POC's) in the wastewater streams even after the well-established conventional treatment is a threat to human health, aquatic entities, and constitute a formidable challenge for the ecological security. In this regard, hydrodynamic cavi-tation based advanced oxidation treatment has attracted extensive attention towards removal of such micro scale pollutants from wastewater streams in the present scenario. Hence, the present work demonstrates the design and application of a rotating hydrodynamic cavitation (RHC) reactor with stator-rotor arrangement for effective degradation of organic micropollutants (triclosan being taken as the target pollutant) from tertiary effluents occurring in the pharmaceutical sector. The process performance was evaluated through optimization of geo-metric parameters of the reactor, various operating parameters as well as by studying the sole and synergistic performance of the HC process combined with other AOPs. The maximum degradation of Triclosan (TCS) ach-ieved by RHC alone was found to be 35.2 % and in synergism, with ozone, a maximum of 97.6 % degradation was observed. Further, to ensure the mineralization of the components, total organic carbon (TOC) contents of the samples were measured and the degradation pathway was predicted through LC-MS analysis. The techno-economic feasibility of the process were understood through economic and energetic analysis and technology transfer was done for replicating the same study for a pilot scale reactor.
Keywords: Advanced oxidation process; Hydrodynamic cavitation; Micropollutant; Pharmaceutical effluent; Tertiary treatment